Association of Traffic Air Pollution with Respiratory Symptoms among Adolescents in Yazd, Iran: Based on Global Asthma Network 2020 Cross-sectional Study - Abdolhamid Jafarinodoshan; Azam Golzar; Hossein Gharechahi; Nasrin Behniafard; Zahra Nafeiy (Journal of Pediatrics Review)
Background: The relationship between Traffic Air Pollution and asthma symptoms in adolescents is controversial. Objectives: This study investigates the impact of traffic air pollution on asthma symptoms among adolescents aged 13-14 years in Yazd City, Iran. Methods: As part of the Global Asthma Network in Yazd City, Iran, a cross-sectional study was conducted in 2020 involving 5141 adolescents from 48 schools selected via cluster sampling. The study assessed the association between self-reported truck traffic exposure and respiratory symptoms. Results: Approximately, 31% of adolescents reported frequent exposure to heavy goods vehicles, with a significant association found between truck traffic and asthma symptoms (P=0.001). However, no significant associations were observed between housing types, floor numbers, and asthma (P=0.15 and P=0.11, respectively). Additionally, a significant relationship existed between truck traffic intensity and severe asthma symptoms (P=0.18). Conclusion: Traffic-related air pollution had a notable impact on asthma symptoms, particularly among male adolescents in Yazd City, Iran.